The Effect of Contextual Teaching and Learning and Motivation Against the Understanding of Adzkia University Students In the Course of Basic Concepts of Elementary Biology - Elva Zuleni (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of Contextual Teaching and Learning (CTL) and Motivation methods on the understanding of Adzkia University students in the basic concepts of elementary biology course. The type of research conducted was a pseudo-experiment with a factorial design of 2 x 2. The research population was first semester students of Adzkia University. Research samples of class A and class B students. Simple random sampling technique. The research data were obtained from questionnaires of motivation and concept understanding. Data were analyzed with Anova. For hypothesis testing, there is a significant influence between the CTL method and motivation in influencing the understanding of Adzkia University students in the basic concepts of elementary biology course. The conclusion of this study is that there is an effect of CTL method and motivation on the understanding of Adzkia University students in the basic concepts of elementary biology course. This means that the CTL method and motivation affect the understanding of the concept.